PENINGKATAN KETERAMPILAN MENULIS KARANGAN EKSPOSISI MENGGUNAKAN PENDEKATAN PROSES DI KELAS IV SEKOLAH DASAR - Nur Hidayati; Siti Halidjah; Endang Uliyanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research had purposed to describe the increase of exposition writing skills by using process approach of IV students at MIS Nahdatul Ulama III Pontianak. In this research, the researcher used descriptive method and classroom action research (CAR). The subject was students of class IV B MIS Nahdatul Ulama III  which has total 19 students consist of 11 male students and 8 female students. The technique of data collection was direct observation with observation paper for students which explained in performance indicator and also observation paper for the teacher as the tool. Students’ skill in exposition writing have increased from cycle 1 to cycle 2 even cycle 2 to cycle 3, students’ average score that reached the indicator in cycle 1 was 10,2 became 13,4 in cycle 2 or increased as much as 3,2 and the average score that reached the indicator in cycle 2 was 13,4 became 17 in cycle 3 or increased as much as 3,6. It means the use of process approach can applied in Bahasa Lessons to increase the students’ writing skill especially exposition writing. Keywords : Classroom action research, Process approach, Writing skill